FREEDOM OF EXPRESSION AND THE “MARGIN OF APPRECIATION” OR “MARGIN OF DISCRETION” DOCTRINE - Ghantous, Marie (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2018)
When an international court decides to keep certain information confidential and orders a ban of any publicity upon them, does it have to abide by the requirements of necessity and proportionality? These requirements have been established by the different human rights conventions and by the jurisprudence of the human rights courts, and human rights bodies. However, for the evaluation of the requirements of necessity and proportionality, states dispose of certain margin of appreciation. International criminal courts might invoke the margin of appreciation doctrine for the same reasons. This paper explores the doctrine of the margin of appreciation recognized to states while assessing a situation before curtailing freedom of expression. After exploring the margin of appreciation doctrine, its justification, the criticism that it faces and the scope of its application, it appeared that it is a well-established and well-accepted doctrine, despite its disadvantages. The relevant case law was then studied in an attempt to come up with a theory concerning its extension to international criminal courts. However, the studied literature or case law was inconclusive. There could be a legal gap in this field. In any case, it seems that international law offers no protection of individuals’ rights at this level in particular. The only recourse open is an appeal, but before the same court. It is clear that checks and balance procedures are not available in what concerns international criminal courts. If a state has a margin of discretion, at least we know that internal remedies and procedures are available, and that they hinder abuse attempts, which is not the case in international criminal courts. This is perhaps a weakness that makes peoples rather uncomfortable about international criminal justice despite the huge relief to see international crimes tried and punished.